The strategic value of crop diversification in Zambia - Mzyece, Agness (Kansas State University, 2020)
This study examines the profitability of crop diversification in Sub-Saharan Africa. Crop diversification means growing different crops or using different cropping systems. It has been shown to provide risk management advantages and to lead to cost reduction in the presence of scope economies. Some countries and economic development organizations are, therefore, promoting crop diversification. However, crop diversification has been shown to be associated with a reduction in productivity and profitability due to foregone efficiency benefits from economies of scale. As a result, some countries, such as Rwanda, have adopted crop specialization policies. In examining the effects of crop diversification on farm performance, previous research has employed various indices to quantify diversification. These indices are based on the number of crops grown and their relative abundance. Although the indices provide a good aggregate measure of diversification, they also assume homogeneity in diversification strategies among farmers who have the same number and relative abundance of crops even though the crops grown may be different. Using indices, therefore, ignores differences in economies of scope among heterogeneous or homogeneous crop combinations and their related profitability. It would seem that prior research has not explored the issue of crop diversification adequately because of crop diversification’s definitional constraints. Against this backdrop, the research problem that this study seeks to address is premised on the fact that different crop combinations may be associated with different performance outcomes. Therefore, this study recognizes diversification not in number of crops, but the types of crops in a farmer’s production ‘portfolio’. We call these portfolios farm enterprise structures. An enterprise structure is a combination of unique crop enterprises that make up the farm. The specific research question that the study addresses is: To what extent do enterprise structures influence profitability? The main objective of the study is to identify combinations of enterprise structures and their related profitability. Differences in enterprise structure profitability could improve our understanding of existing cropping patterns and help to identify ways of strategically design enterprise structures to achieve higher profitability given farmer’s realities. We use secondary data from Zambia’s 2015 Rural Agricultural Livelihood Survey (RALS). RALS is a country-wide survey of agricultural producers with a sample size of 7,934 randomly selected households. We utilize the Gaussian/Ordinary Least Squares (OLS) regression model to test the significance of the effect associated with adopting different enterprise structures, and to examine their contributions to profitability. The results show statistically significant differences in demographic, socio-economic and production characteristics among farmers pursuing different enterprise structures. The results also show regional variations in the distribution and profitability of enterprise structures. This is understandable because of differences in regional agro-ecological conditions. The results further show that enterprise structures significantly influence profitability to varying degrees, suggesting that some crop portfolios may have higher profitability than others even though they may have the same number of crops. Diversification recommendations based on enterprise structures are, therefore, likely to be more effective than those based on indices.
Keywords: Crop diversification; Enterprise structure; Profitability